Effects of enzyme concentration, temperature, pH and time on the degree of hydrolysis of protein extract from viscera of tuna (Euthynnus affinis) by using alcalase - Salwanee, S.; Wan Aida, W.M.; Mamot, S.; Maskat, M.Y. (Universiti Kebangsaan Malaysia, 2013)
Protein from viscera of tuna was extracted by using water at ratio of viscera to water of 1:1 (w/v) and freeze-dried. The protein was found to be high in glycine (9.6%), arginine (9.2%), alanine (7.0%), lysine (7.2%) and leucine (7.0%). A study was then carried out to determine the effect of alcalase concentration, temperature, pH and incubation time on degree of hydrolysis (DH) during hydrolysis by using single factor experiment. The hydrolysis of viscera protein extract (VPE) was carried out at concentrations of 1.0, 1.5 and 2.0%. The DH of hydrolysates was significantly (p<0.05) increased when enzyme concentration was increased from 1.0% to 1.5% but became constant at concentration exceeding 1.5%. An enzyme concentration at 1.5% was subsequently used in the study of the effect of the other parameters. It was found that the value of the DH also increased when the temperature was increased from 30 to 40°C. However, the hydrolysis at higher temperature (60°C) produced lower DH. Prolonging the time of incubation from 60 min up to 240 min significantly (p< 0.05) increased the DH. As for pH, there were no significant effects observed.